2022
DOI: 10.1097/shk.0000000000002027
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and Infiltrating T-Cells Adopt Long-Term, Age-Specific, Transcriptional Changes After Traumatic Brain Injury in Mice

Abstract: Aged traumatic brain injury (TBI) patients suffer increased mortality and long-term neurocognitive and neuropsychiatric morbidity compared with younger patients. Microglia, the resident innate immune cells of the brain, are complicit in both. We hypothesized that aged microglia would fail to return to a homeostatic state after TBI and adopt a long-term injury-associated state within aged brains compared with young brains after TBI. Young and aged male C57BL/6 mice underwent TBI via controlled cortical impact v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
(81 reference statements)
2
12
0
Order By: Relevance
“…Long-term inflammatory responses after TBI have been reported by our group and others (Chen, Islam et al 2023, Obenaus, Rodriguez-Grande et al 2023). Given the phenotypic changes in astrocytes we investigated if microglia (via IBA1 immunohistochemistry) within the ipsilateral CC exhibited an activated morphology characteristic of inflammatory states.…”
Section: Resultssupporting
confidence: 72%
“…Long-term inflammatory responses after TBI have been reported by our group and others (Chen, Islam et al 2023, Obenaus, Rodriguez-Grande et al 2023). Given the phenotypic changes in astrocytes we investigated if microglia (via IBA1 immunohistochemistry) within the ipsilateral CC exhibited an activated morphology characteristic of inflammatory states.…”
Section: Resultssupporting
confidence: 72%
“…Inhibiting CCR3 in T cells attenuates this T-cell migration into the brain and alleviates microgliosis in aged mouse brains (14). In line with current literature, previous work in our laboratory indicated that microglia from aged mouse brains demonstrate more significant levels of activation after TBI than microglia from young mouse brains after TBI (6). Single-cell RNA sequencing (scRNAseq) showed that in the chronic phase of TBI, microglia from aged mouse brains still significantly upregulate genes, including S100a9, S100a8, Ccl2, Ccl3, and Pdgfb, that are involved in T-cell migration and chemotaxis, inducing the accumulation of T cells within aged brains (6).…”
Section: Introductionssupporting
confidence: 89%
“…However, the underlying pathophysiologic mechanisms of these differential outcomes remain elusive. Multiple findings have indicated that the adaptive immune system plays a role in pathologic consequences within the CNS after brain injury in aged subjects (6,22,23). Understanding the role of the adaptive immune system after TBI is a critically unmet research need as it has the potential to pinpoint age-specific therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations